Combined α2- and D2-receptor blockade activates noradrenergic and dopaminergic neurons, but extracellular dopamine in the prefrontal cortex is determined by uptake and release from noradrenergic terminals - Sagheddu, Claudia; Devoto, Paola; Aroni, Sonia; Saba, Pierluigi; Pistis, Marco; Gessa, Gian Luigi (Frontiers in Pharmacology, 2023)
Experimental and clinical evidence indicates a deficit of release and function of dopamine in schizophrenia, and suggests that α2-adrenoceptor antagonists rescue dopamine deficit and improve the antipsychotic efficacy of D2-receptor antagonists.In anesthetized male rats, we investigated how the blockade of α2and D2 receptors by atipamezole and raclopride, respectively, modified the firing of noradrenergic neurons in the locus coeruleus (LC) and dopaminergic neurons in the ventral tegmental area (VTA). In freely moving rats, we studied by microdialysis how atipamezole and raclopride modified extracellular noradrenaline, dopamine, and DOPAC levels in the medial prefrontal cortex (mPFC).2 This is a provisional file, not the final typeset article When given alone, atipamezole activated LC noradrenaline but not VTA dopamine cell firing.Combined with raclopride, atipamezole activated dopamine cell firing above the level produced by raclopride. Atipamezole increased extracellular dopamine to the same level, whether given alone or combined with raclopride. In the presence of the noradrenaline transporter (NET) inhibitor, atipamezole combined with raclopride increased extracellular dopamine way above the level produced by either compound given singly.The results suggest that a) D2-autoreceptor blockade is required for LC noradrenaline to activate VTA cell firing; b) dopamine released from dopaminergic terminals is taken by NET; c) elevation of extracellular dopamine in the mPFC is the resultant of dopamine uptake and release from noradrenergic terminals, independent from dopaminergic cell firing and release; d) LC noradrenergic neurons are an important target for treatments aimed to improve prefrontal deficit of dopamine in neuropsychiatric pathologies.